Tensor Coupled Learning of Incomplete Longitudinal Features and Labels for Clinical Score Regression - Xiao, Qing (IEEE transactions on pattern analysis and machine intelligence, 2024)
Longitudinal data with incomplete entries pose a significant challenge for clinical score regression over multiple time points. Although many methods primarily estimate longitudinal scores with complete baseline features (i.e., features collected at the initial time point), such snapshot features may overlook beneficial latent longitudinal traits for generalization. Alternatively, certain completion approaches (e.g., tensor decomposition technology) have been proposed to impute incomplete longitudinal data before score estimation, most of which, however, are transductive and cannot utilize label semantics. This work presents a tensor coupled learning (TCL) paradigm of incomplete longitudinal features and labels for clinical score regression. The TCL enjoys three advantages: 1) It drives semantic-aware factor matrices and collaboratively deals with incomplete longitudinal entries (of features and labels), during which a dynamic regularizer is designed for adaptive attribute selection. 2) It establishes a closed loop connecting baseline features and the coupled factor matrices, which enables inductive inference of longitudinal scores relying on only baseline features. 3) It reinforces the information encoding of baseline data by preserving the local manifold of longitudinal feature space and detecting the temporal alteration across multiple time points. Extensive experiments demonstrate the remarkable performance improvement of our method on clinical score regression with incomplete longitudinal data